The Afro-South American brachiopod Castellaroina Boucot from the Silurian of the Argentine Precordillera: its origin and phylogenetic relationships - Benedetto, Juan Luis Arnaldo (2015)
The Silurian genus Castellaroina and related leptostrophiids are reviewed and partially redescribed from the La Chilca, Los Espejos and Tambolar Formations of the Argentine Precordillera. The La Chilca Formation contains Eostropheodonta chilcaensis chilcaensis (Benedetto) and the new subspecies Eostropheodonta chilcaensis parvula of Rhuddanian and Aeronian–Telychian age, respectively. Castellaroina is represented by the type species Castellaroina fascifer (Kayser) and the new species Castellaroina fuertensis, both from beds of essentially Ludlow age. Parsimony analysis of the family Leptostrophiidae indicates that Eostropheodonta hirnantensis is closest to the outgroup (Rafinesquina) and ancestral to the entire leptostrophiid clade. Viodostrophia, Palaeoleptostrophia, Eostropheodonta and Castellaroina form a basal group characterized by having denticular plates and lacking hinge denticulation, and clearly differ from the derived denticulate forms that become dominant during the Devonian. After the late Hirnantian biotic crisis, a local radiation of endemic leptostrophiids took place in the Afro–South American Realm. Stratigraphic and morphologic evidence support that Eostropheodonta hirnantensis—present in the Hirnantian communities of the Precordillera basin—gave rise to the lineage leading to Castellaroina fuertensis nov. sp. and Castellaroina fascifer, being Eostropheodonta chilcaensis parvula nov. subsp. and Eostropheodonta chilcaensis chilcaensis intermediate forms. It is suggested that heterochronic processes played an important role in directing morphological changes in this evolutionary lineage.